1998
DOI: 10.1042/bj3320367
|View full text |Cite
|
Sign up to set email alerts
|

Salicortin: a repeat-attack new-mechanism-based Agrobacterium faecalis β-glucosidase inhibitor

Abstract: Salicortin, a natural product abundant in most members of the Salicaceae family, is a mechanism-based inactivator of Agrobacterium faecalis beta-glucosidase. Inactivation is delayed in the presence of competitive inhibitors, thereby demonstrating the requirement for an enzyme-bound salicortin before inactivation. Product studies suggest that inactivation proceeds via a quinone methide intermediate formed by the fragmentation of the aglycone of salicortin while it is bound to the enzyme. Tryptic digest and HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
(29 reference statements)
2
16
0
Order By: Relevance
“…For HCC, two metabolic routes have been suggested in the literature, which both involve irreversible covalent binding to proteins. Clausen et al (1990) found that HCC can form quinone methides which attack and deactivate glucosidases (Zhu et al, 1998). Alternatively, if catechol is derived from the HCC moiety, as shown in our work and previously (Pearl and Darling, 1970;Ruuhola et al, 2003), this compound could also form quinones and react with proteins (Appel, 1993).…”
Section: Localization and Transport Of Salicinoid Metabolites In Gypssupporting
confidence: 76%
See 1 more Smart Citation
“…For HCC, two metabolic routes have been suggested in the literature, which both involve irreversible covalent binding to proteins. Clausen et al (1990) found that HCC can form quinone methides which attack and deactivate glucosidases (Zhu et al, 1998). Alternatively, if catechol is derived from the HCC moiety, as shown in our work and previously (Pearl and Darling, 1970;Ruuhola et al, 2003), this compound could also form quinones and react with proteins (Appel, 1993).…”
Section: Localization and Transport Of Salicinoid Metabolites In Gypssupporting
confidence: 76%
“…Salicinoids have been suggested to be activated by degradation to the toxic metabolite saligenin (reviewed in Pentzold et al, 2014) or catechol, which may oxidize to form reactive quinones (Ruuhola et al, 2001). These reactions were proposed based on the results of in vitro experiments (Clausen et al, 1990;Julkunen-Tiitto and Meier, 1992;Ruuhola et al, 2003) and studies with bacteria (Sonowal et al, 2013;Zhu et al, 1998) or vertebrates (Knuth et al, 2013;McLean et al, 2001), but the pathways of salicinoid metabolism in poplar-feeding arthropods are still not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Their biological activity has therefore been proposed to be a result of smaller toxic products such as phenol and catechol (Clausen et al 1989). However, salicortin can also act as an inactivator of β ‐glucosidase from Agrobacterium faecalis (Zhu et al 1998), a finding that emphasizes the complex nature of these phenolics.…”
Section: Introductionmentioning
confidence: 99%
“…Such inhibitory behavior is a possibility since the reactive ortho -quinone methide conceivably could react with a nucleophile in the GUS enzyme, similar to what has been previously observed for a bacterial glucosidase treated with a quinone methide-forming natural product. 87 The same group has also previously prepared near-infrared 88 and fluorescent 89 probes for GUS using a similar scaffold, and those compounds proved helpful while testing 18 as a potential PET probe for GUS. Although no enzyme kinetic values were reported, cell studies with a nonradioactive fluorescein-labeled analogue of [ 127 I] 18 showed that cells expressing GUS on their surface were irreversibly fluorescently labeled.…”
Section: Ec 32: Glycosylasesmentioning
confidence: 99%